Association of Basic Sanitation Access and Personal Hygiene with Skin Disease Occurrence among Flood-Affected Communities in Padang City, Indonesia - Emy Indaryani; Darwel (Knowledge and Environmental Science for Living and Global Health, 2026)
Flooding is a hydrometeorological disaster that increases the risk of skin diseases due to poor sanitation and inadequate personal hygiene. This study aimed to analyze the relationship between access to basic sanitation and personal hygiene with the occurrence of skin diseases among flood-affected communities in Padang City in 2025. A quantitative study with a cross-sectional design was conducted involving 150 respondents selected using simple random sampling. Data were collected through structured questionnaires and observations and analyzed using chi-square tests and logistic regression. The results showed that 62.7% of respondents experienced skin diseases. There were significant associations between access to basic sanitation (p = 0.003) and personal hygiene (p = 0.001) with the occurrence of skin diseases. Multivariate analysis indicated that inadequate sanitation was associated with a 2.4-times higher likelihood of skin diseases (OR = 2.40; 95% CI: 1.35–4.26), while poor personal hygiene was associated with a 3.1-times higher likelihood of skin diseases (OR = 3.10; 95% CI: 1.68–5.72). It was concluded that personal hygiene was the most dominant factor associated with the occurrence of skin diseases. Therefore, integrated hygiene-based interventions and the provision of adequate sanitation are important to reduce the risk of skin diseases among flood-affected communities.